PENGEMBANGAN VIDEO ANIMASI PEMBELAJARAN PADA MATERI TUMBUH KEMBANG HEWAN DI SEKOLAH DASAR - Melati gumilang sari , yusni arni, jenny andriyani parla gustita,Lusdini, Mawar Fitriah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This reseach aims to find vout what the design steps are development of animated science learning videos based on animated videos on the material animal growth and development, how appropriate are science – based learning animation videos? Videos on animal growth and development material, and the effectiveness of animated learning videos video based science on animal growth and development material for SD NEGERI 3 TANJUNG BATU student. The type of research used is research and (R&D). model the development used in this rsearch is the ADDIE model which consists of (analisis, design, development, implementation and evaluation). Development result video – based interactive science learning videos on animal growth and development material growth and development material in class V shows a significant difference before and after use animated leraning videos based on science videos and have been tested that learning videos science – based interactive videos are very affective as learning media. The aim of this research is tools determine the effect of using tools audio visual learning into learning topics of growth and development animals on the learning achievwment of elementary school student in fifth grade. The bresearch is an example of qualitative research. Qualitative research, visuals in learning material about animal growth and development toward result studying class V student of SD NEGERI 3 TANJUNG BATU.